What are survivorship care plans failing to tell men after prostate cancer treatment?. Issue 7 (23rd March 2021) - Choi, Youngjee; Smith, Katherine C.; Shukla, Aishwarya; Blackford, Amanda L.; Tran, Phuoc T.; Peairs, Kimberly S.; DeMarco, Thomas M.; Choflet, Amanda; Farling, Kristen; Kelso, Madeline; Carducci, Michael A.; Mayonado, Nancy; et al.
Abstract: Background: Survivorship care plans contain important information for patients and primary care physicians regarding appropriate care for cancer survivors after treatment. We describe the completeness of prostate cancer survivorship care plans and evaluate the concordance of follow‐up recommendations with guidelines. Methods: We analyzed 119 prostate cancer survivorship care plans from one academic and one community cancer center, abstracting demographics, cancer/treatment details, and follow‐up recommendations. Follow‐up recommendations were compared with the American Cancer Society (ACS), American Society of Clinical Oncology (ASCO), and National Comprehensive Cancer Network (NCCN) guidelines. Results: Content in >90% of plans included cancer TNM stage; prostate‐specific antigen (PSA) at diagnosis; radiation treatment details (98% of men received radiation); and PSA monitoring recommendations. Potential treatment‐specific side effects were listed for 82% of men who had surgery, 86% who received androgen deprivation therapy (ADT), and 97% who underwent radiation. The presence of posttreatment symptoms was noted in 71% of plans. Regarding surveillance follow‐up, all guidelines recommend an annual digital rectal exam (DRE). No plans specified DRE. However, all 71 plans at the community site recommended at least annual follow‐up visits with urology, radiation oncology, and primary care. Only 2/48 plans at the academic site specified follow‐up visits. All guidelines recommend PSA testing every 6–12 months for 5 years, then annually. For the first 5 years, 90% of plans were guideline‐concordant, 8% suggested oversurveillance, and 2% were incomplete. In men receiving ADT, ACS and ASCO recommend bone density imaging and NCCN recommends testosterone levels. Of 77 men on ADT, 1% were recommended bone density imaging and 16% testosterone level testing. Conclusions: While care plan content is more complete for demographic and treatment summary information, both sites had gaps in reporting posttreatment symptoms and ADT‐related testing recommendations. These findings highlight the need to improve the quality of information in care plans, which are important in communicating appropriate follow‐up recommendations to patients and primary care physicians.